How much is the patient's quality of life impaired in the early stages of stroke? - Jovanović Aleksandar; Ušjak Miroslav; Niković Jelena; Pejin Radoslav; Tomić Sanja (Association of Nurses Technicians and Midwives, 2022)
Introduction: Stroke is one of the leading causes of adult disability and certainly the most significant single cause of neurological disability. Aim: To examine the quality of life of patients after a stroke by analyzing the physical and mental condition, as well as social skills from the aspect of individual, family, professional and life on the broader community. Methodology: The research is designed as a prospective study. The sample consisted of 20 patients with stroke (experimental group) and patients without stroke (control group), treated at the Clinic for Medical Rehabilitation of the Clinical Center of Vojvodina. The National Institute of Health Stroke Scale (NIHSS), the Modified Bartel Index, the Rankin Scale (mRS) and the Mini-Mental State Exam (MMSE) were used to assess neurological status, functional and cognitive status. In addition, the SF-36 Short Form Health Questionnaire and the Stroke Impact Scale (SIS) were used to assess the quality of life. Results: In all domains of SIS and the overall score, statistically significant differences were found between patients with stroke, compared to those without. The most significant differences were found in handicap, arm, and daily activities. The minor differences, but still statistically significant, were found in communication, memory, and emotions. Conclusion: Patients' quality of life after a stroke is significantly impaired, and physical functioning is most affected.